Tanggung Jawab Fikih: Memperkuat Kedudukan Perempuan Dengan Migrasi - Teguh Prawiro (STIT Muslim Asia Afrika, 2019)
Migration is the issue that widely discussed by almost of Indonesian society. Death penalty and trafficking in personsthat faced Indonesian migrant workers, make aware of how acute the problem of migration has been.Because of that, now, migration is our common problem.On the other side, the phenomenon of migration shows a shift in the role and position of women in the family. During the time women are often placed in a weak position before men. The role of breadwinners in the family is always taken by men. The religious teachings that discriminates against women in the family is almost accepted by the majority of Muslims. While in practice, with the migration many women who take the role of breadwinners in the family. Therefore, it is necessary to reform thoroughly the mechanism and protection of Indonesian migrant workers, the majority of them are women. Therefore, fiqh perspective should be a part in providing solutions to problems related to migration in Indonesia.